The histone-like protein HU binds specifically to DNA recombination and repair intermediates - Kamashev, D. (Oxford University Press, 2000)
The heterodimeric HU protein associated with the Escherichia coli nucleoid shares some properties with histones and HMG proteins. HU binds DNA junctions and DNA containing a nick much more avidly than double-stranded (ds-) DNA. Cells lacking HU are extremely sensitive to γ irradiation and we wondered how HU could play a role in maintaining the integrity of the bacterial chromosome. We show that HU binds with high affinity to DNA repair and recombination intermediates, including DNA invasions, DNA overhangs and DNA forks. The DNA structural motif that HU specifically recognizes in all these structures consists of a ds-DNA module joined to a second module containing either ds- or single-stranded (ss-) DNA. The two modules rotate freely relative to one another. Binding specificity results from the simultaneous interaction of HU with these two modules: HU arms bind the ds-DNA module whereas the HU body contacts the ‘variable’ module containing either ds- or ss-DNA. Both structural motifs are recognized by HU at least 1000-fold more avidly than duplex DNA.